2019
DOI: 10.3390/su11010200
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact and Risk Assessment of Sand and Dust Storms (SDS) on the Oil and Gas Industry in Kuwait

Abstract: There is a lack of published research on the economic effect and the risk associated with sand and dust storms (SDS) worldwide. The objectives of this study are to estimate the economic impact of SDS on the oil and gas industry in Kuwait, to estimate a risk index for each loss, and to recommend a sustainable system for the mitigation of the damaging effects and economic losses of infrastructures. Hot spots of wind erosion, wind corridors, and dust frequency and severity formed the basis to locate the most susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…This study also has found a positive and significant relationship between the FSTs and the rate of road accidents. Therefore, this study supports the findings of the majority of previous studies [71][72][73][74][75][76][77][78]85,86]. For example, Al-Hemoud et al [85] stated that sandstorm was a significant contributory factor to RTAs in Gulf Areas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study also has found a positive and significant relationship between the FSTs and the rate of road accidents. Therefore, this study supports the findings of the majority of previous studies [71][72][73][74][75][76][77][78]85,86]. For example, Al-Hemoud et al [85] stated that sandstorm was a significant contributory factor to RTAs in Gulf Areas.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, this study supports the findings of the majority of previous studies [71][72][73][74][75][76][77][78]85,86]. For example, Al-Hemoud et al [85] stated that sandstorm was a significant contributory factor to RTAs in Gulf Areas. Moreover, Maghrabi et al [87] conducted a study on the impact of dust on road accidents in Saudi Arabia in March 2009 and found extensive damage to vehicles and a high number of RTAs.…”
Section: Discussionsupporting
confidence: 91%
“…(3) Set the values of the allowable deviations δ 1 and the allowable variation of the weight vector δ 2 (for Equations (11) and (12)), select the type of metric…”
Section: E (Qe) Methodsmentioning
confidence: 99%
“…Solve the problem of maximizing the objective function µ 0 (x) taking into account the constraints imposed in Equations (7) and (8), (9) and (10), and (11) and (12), determine the current solutions: x(β)-values of the control (regime) parameters, µ 0 (x(β)) criterion values; µ 1 (x(β)), . .…”
Section: E (Qe) Methodsmentioning
confidence: 99%
See 1 more Smart Citation